Pulpal lesions in normal and cyclosporin a treated rats - Lopes, Márcio Ajudarte; Spolidório, Luis Carlos [UNESP]; Line, Sérgio Roberte Peres; De Almeida, Oslei Paes (Elsevier, 1997)
The objective of this study was to examine the development of pulpal lesions in the lower molar of control and cyclosporin A (CyA) treated rats. The pulps of the first lower molars of 20 normal and 20 CyA treated rats were exposed and left open into the oral cavity. Five animals of each group were killed at 7, 14, 21, and 28 days after the pulp exposure. The specimens were sectioned sagittally at a thickness of 7 μm and stained with hematoxylin and eosin. The pulpal lesions were similar for both normal and CyA treated rats in all studied periods and the differences between both groups were not statistically significant by the Student t test at the 5% (0.05) level of significance, indicating that the immunosuppression did not alter the evolution of the inflammatory process. Copyright © 1997 by The American Association of Endodontists.
Keywords: cyclosporin; immunosuppressive agent; animal; comparative study; disease course; drug effect; male; pathology; rat; time; tooth pulp; tooth pulp disease; Wistar rat; Animals; Cyclosporine; Dental Pulp; Dental Pulp Necrosis; Disease Progression; Immunosuppressive Agents; Male; Rats; Rats, Wistar; Time Factors